Próba cybernetycznej interpretacji problemu zapasów na przykładzie huty żelaza - Jaworski, Janusz (Wydział Prawa i Administracji UAM, 1971)
The present article is an attempt at transforming the technical-economical problem of inventory into cybernetic terms. The analogy between functioning of the inventory system in production process and functioning of natural energetic resources in living organisms was also indicated. The inventory problem was presented in the light of cyberentic regulation theory and theory of reliability. The regulating influence of inventory on the course of production processes as well as the dependence between inventory and reliability of the iron foundry as a cyberentic system were shown.
An Attempt at Cybernetic Interpretation of Inventory Problems on the Example of an Iron Foundry